The Impact of Overcapacity on the Fulfillment of Prisoners' Rights to Health Services in Class I Malang Prison Institutions - Zainah Al Widad Muarif; Gelar Ali Ahmad (Universitas Negeri Surabaya, 2024)
Overcapacity is a condition where the number of prisoners exceeds the available capacity. The problem of overcapacity is a serious issue related to human rights, because the condition of overcapacity certainly causes the living conditions of prisoners to be inappropriate, in a situation of overcapacity the prison has a very limited space for movement so that in a narrow room increases the risk of health problems that will quickly spread between prisoners. The problem of overcapacity was studied to find out in fact how the impact of overcapacity on the fulfillment of the right to obtain health services for prisoners at the Class I Correctional Institution in Malang, along with knowing what are the obstacles in fulfilling the right to obtain health services for prisoners. The research method uses empirical legal research or sociological juridical with a qualitative approach as a writing guide. The results of this study concluded that the impact of overcapacity on the fulfillment of health services for prisoners, one of which is related to the general health services of the inpatient unit, not all prisoners with indications of serious illness will be hospitalized due to insufficient space, the lack of this has resulted in the emergence of obstacles in the fulfillment of health services, namely the lack of complete facilities and infrastructure, human resources in the form of medical personnel and the lack of awareness of prisoners to maintain environmental hygiene which has an impact on the health of prisoners.